Enhancing Prime Services through Total Quality Management Strategies: Impacts on the Digital Transformation Process at Islamic Universities - R Kempa; Lamberthus J Lokollo; Djamila Lasaiba; Mohammad Amin Lasaiba; Arman Man Arfa (AL-ISHLAH: Jurnal Pendidikan, 2024)
Total Quality Management (TQM) is a management approach aimed at enhancing the quality of products, services, and organizational processes. In educational administration, TQM involves applying these principles to boost the efficiency and effectiveness of the education system. This study investigates whether TQM implementation improves digital transformation initiatives and service delivery in educational settings. Using a quantitative approach with the Structural Equation Model (SEM), this research measures and analyzes the relationships between TQM, Digital Transformation, and Prime Services. The study population comprises students from the Faculty of Tarbiyah who have completed at least three semesters, providing them with sufficient experience to assess TQM's effectiveness. Nonprobability quota sampling is used to select respondents based on predetermined criteria. The findings reveal that all reflective indicator variables in the outer model are valid, with high reliability demonstrated by composite reliability and Cronbach's alpha values. The inner model testing shows that exogenous variables can be explained by endogenous variables, including TQM (X1), Digital Transformation (X2), and Prime Services (X3). The results indicate that TQM significantly impacts digital transformation and the enhancement of prime services in education. Recommendations for educational administrators include strengthening TQM principles, increasing investment in digital technology, and focusing on prime services to students. These steps can improve operational efficiency, educational quality, and responsiveness to student needs in the digital era.